2023
DOI: 10.1155/2023/1120569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructural Characteristics on Wear and Corrosion Behaviour of Si3N4-Reinforced Al2219 Composites

Abstract: The fabrication of the Al2219 + Si3N4 composites was done by means of stir casting process. The specimen was subjected to microstructural studies. The density of Si3N4 employed in the fabrication of the composites has been evaluated. Generally, the density of the composites increases as the weight percent of Si3N4 increases. TGA and DTA were performed at temperatures ranging from 30°C to 800°C, with some mass loss noted as well as the thermal stability of an AA2219 matrix improved. Under various parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…As can be seen in Figure 8, they also reported abrasive wear for the composite and adhesion for the matrix alloy. In another study on AA2219/Si 3 N 4 composites with 3 Wt.%, 6 Wt.%, and 9 Wt.% of reinforcement, it was shown that the addition of 6 Wt.% of Si 3 N 4 to the alloy exhibited optimum wear behavior at all applied loads and velocities [80]. Similar trends in wear rate results were also reported by Manjunatha et al [78].…”
Section: Ceramic Reinforcementssupporting
confidence: 79%
“…As can be seen in Figure 8, they also reported abrasive wear for the composite and adhesion for the matrix alloy. In another study on AA2219/Si 3 N 4 composites with 3 Wt.%, 6 Wt.%, and 9 Wt.% of reinforcement, it was shown that the addition of 6 Wt.% of Si 3 N 4 to the alloy exhibited optimum wear behavior at all applied loads and velocities [80]. Similar trends in wear rate results were also reported by Manjunatha et al [78].…”
Section: Ceramic Reinforcementssupporting
confidence: 79%
“…In comparison to the SiC reinforced composite, the TiB 2 reinforced composite demonstrated superior mechanical and tribological properties. 36 In separate studies, Manjunatha et al 37 and Subramanian et al 38 investigated the tribological characteristics of Si 3 N 4 -aluminum composites. They observed that the rate of wear and corrosion decreased with an increasing weight percentage of Si 3 N 4 in the aluminum matrix.…”
Section: Introductionmentioning
confidence: 99%